Genome mining reveals the prevalence and extensive diversity of toxin–antitoxin systems in Staphylococcus aureus - Xu, Jie; Wang, Ying; Liu, Fang; Duan, Guangcai; Yang, Haiyan (Frontiers in Microbiology, 2023)
Staphylococcus aureus (S. aureus) is a ubiquitous Gram-positive bacterium that is highly pathogenic and adaptive, showing great persistence in the environment. The toxin-antitoxin (TA) system is considered a valuable strategy for bacterial pathogens to survive in stressed environments and plays a crucial role in the defense system. Numerous studies have widely explored the distribution and function of TA systems in clinical pathogens. However, scant information exists regarding the breadth of diversity encompassed by the TA systems and their intricacies of evolution in S. aureus. In this investigation, we conducted a comprehensive in silico survey of 621 isolates obtained from publicly available databases. Through meticulous employment of bioinformatic search and prediction tools, namely SLING, TADB2.0, and TASmania, we delineated a total of 44 distinct TA groups within the genomes of S. aureus. There are a median of seven TA systems in each genome, and three type II TA groups which were found in more than 80% of the strains, including HD, HD_3, and YoeB, others were more sporadic. The majority of predicted TA genes are chromosomally encoded. The Staphylococcal Cassette Chromosomal mec (SCCmec) genomic islands also harbored TA genes. Further functional characterization of the putative TA system could reveal how these widespread prevalent gene modules potentially influence the ecology, virulence, and disease management practices of S. aureus. Our study paves the way for a deeper understanding of these putative TA genes and provides insights for the development of more targeted antimicrobial agents in the future.